Registration of 'KS4719' winter canola. Issue 1 (8th September 2021) - Stamm, Michael; Aiken, Robert; Angadi, Sangu; Damicone, John; Dooley, Scott; Holman, Johnathon; Johnson, Jerry; Kimura, Emi; Larson, Kevin; Lofton, Josh; Santra, Dipak
Abstract: 'KS4719' (Reg. no. CV‐28, PI 697260) is a winter canola cultivar ( Brassica napus L.) that possesses superior winterhardiness, greater lodging resistance, and improved pod shattering. KS4719 first drew attention when a devastating cold snap in November 2014 caused much of the winter canola crop to winter kill. KS4719 winter survival scores were 15 and 121% greater than the check cultivars 'Sumner' and 'Wichita', respectively, at Kansas State University's lone surviving trial site in northern Oklahoma. In the National Winter Canola Variety Trial (NWCVT) testing, the winter survival score of KS4719 was equivalent to 'Torrington', the most winter hardy commercially available cultivar. Across two sites of the 2015–2016 Great Plains Canola Variety Trial (GPCVT), KS4719 showed significantly improved pod shatter compared with the check cultivars. Across 14 NWCVT sites in the U.S. Great Plains, grain yield did not differ from the check cultivars; however, KS4719 did yield 5 and 19% more than 'Surefire' and Torrington, respectively, the two most recent cultivar releases from the Kansas State University canola breeding program. Over five site‐years, KS4719 averaged 9% lodging, while Torrington averaged 19%. It is theorized that the improved lodging resistance of KS4719 comes from a stem and root system that is less prone to rotting in saturated soils. Greater winterhardiness is in part due to protection of the lower stem (rosette) throughout the winter months. Core Ideas: KS4719 winter canola is a new cultivar release from Kansas State University. KS4719 possesses exceptional winterhardiness. KS4719 is less prone to lodging in saturated soils.